HLA in North Colombia Chimila Amerindians (2018)
HLA-A,-B,-C,-DRB1 and -DQB1 alleles have been studied in Chimila Amerindians from Sabana de San Angel (North Colombian Coast) by using high resolution molecular typing. A frequent extended haplotype was found:HLA-A*24:02-B*51:10-C*15:02-BRB1*04:07-DQB1*03:02 (28.7%) which has also been described in Amerinndian Mayos Mexican population (Mexico, California Gulf, Pacific Ocean). Other haplotypes had already been found in Amerindians from Mexico (Pacific and Atlantic Coast), Peru (highlands and Amazon Basin), Bolivia and North USA. A geographic pattern according to HLA allele or haplotype frequencies is lacking in Amerindians, as already known. Also, five new extended haplotypes were found in Chimila Amerindians. Their HLA-A*24:02 high frequencies characteristic is shared with aboriginal populations of Taiwan; also, HLAC* 01:02 high frequencies are found in New Zealand Maoris, New Caledonians and Kimberly Aborigines from Australia. Finally, this study may show a model of evolutionary factors acting and rising one HLA allele frequency (-A*24:02), but not in others that belong to the same or different HLA loci.